TcMYB29a, an ABA-Responsive R2R3-MYB Transcriptional Factor, Upregulates Taxol Biosynthesis in Taxus chinensis - Cao, Xiaoying; Xu, Lingxia; Li, Ludan; Wan, Wen; Jiang, Jihong (Frontiers in Plant Science, 2022)
Paclitaxel (Taxol), a highly modified diterpene agent mainly obtained from Taxus species, is the most widely used anticancer drug. Abscisic acid (ABA) is a well-known stress hormone that plays important roles in the secondary metabolism of plants, and it can also induce the accumulation of taxol in Taxus cell suspension cultures. However, the mechanism behind the regulation of taxol biosynthesis by ABA remains largely unknown. In previous research, a R2R3 MYB transcription factor (TF) TcMYB29a was observed to show a significant correlation with taxol biosynthesis, indicative of its potential role in the taxol biosynthesis. In this study, the TcMYB29a encoded by its gene was further characterized. An expression pattern analysis revealed that TcMYB29a was highly expressed in the needles and roots. Overexpression of TcMYB29a in Taxus chinensis cell suspension cultures led to an increased accumulation of taxol, and upregulated expression of taxol-biosynthesis-related genes, including the taxadiene synthase (TS) gene, the taxane 5α-hydroxylase (T5OH) gene, and the 3′-N-debenzoyl-2′-deoxytaxol-N-benzoyltransferase (DBTNBT) gene as compared to the controls. Chromatin immunoprecipitation (ChIP) assays, yeast one-hybrid (Y1H) assays, electrophoretic mobility shift assays (EMSAs), and dual-luciferase reporter assays verified that TcMYB29a could bind and activate the promoter of TcT5OH. Promoter sequence analysis of TcMYB29a revealed that its promoter containing an AERB site from -313 to -319 was a crucial ABA-responsive element. Subsequently, the ABA treatment assay showed that TcMYB29a was strongly upregulated at 6 h after ABA pretreatment. Furthermore, TcMYB29a was strongly suppressed at 3 h after the methyl jasmonate (MeJA) treatment and was depressed to the platform at 12 h. Taken together, these results reveal that TcMYB29a is an activator that improves the accumulation of taxol in Taxus chinensis cells through an ABA-medicated signaling pathway which is different from JA-medicated signaling pathways for the accumulation of taxol. These findings provide new insights into the potential regulatory roles of MYBs on the expression of taxol biosynthetic genes in Taxus.